2019
DOI: 10.1158/1538-7445.sabcs18-p6-05-10
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-05-10: MicroRNA-137 inhibits cancer progression by targeting DEL-1 in triple negative breast cancer cells, MDA-MB-231

Abstract: Background: This study aimed to investigate the function of microRNA-137 in Del-1 expression in triple negative breast cancer (TNBC) cells and tissues. Methods: The Del-1 mRNA and microRNA levels were measured using a qRT-PCR in breast cancer cells (MDA-MB-231, MCF7, SK-BR3, and T-47D) and tissues from 20 patients with TNBC. The effects of miR-137 on cell proliferation, migration, and invasion were determined using MTT, wound healing, and Matrigel Transwell assays. Results: microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…miR-137 downregulation has been associated frequently with various types of cancer and to a great extent with poor prognostic clinico-pathological parameters and decreased overall survival (OS) [30][31][32][33][34][35]. Studies have shown that miR-137 often performs as a tumor suppressor in gastric [36][37][38][39], colorectal cancer [40,41], cholangiocarcinoma [42], kidney [32,33], ovarian [43], endometrial [44] and non-small cell lung cancer [45,46], melanoma [47,48], triple-negative breast cancer (TNBC) [49,50]. Recent studies, however, have shown that miR-137 is upregulated in lung [51] and bladder cancer [52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-137 downregulation has been associated frequently with various types of cancer and to a great extent with poor prognostic clinico-pathological parameters and decreased overall survival (OS) [30][31][32][33][34][35]. Studies have shown that miR-137 often performs as a tumor suppressor in gastric [36][37][38][39], colorectal cancer [40,41], cholangiocarcinoma [42], kidney [32,33], ovarian [43], endometrial [44] and non-small cell lung cancer [45,46], melanoma [47,48], triple-negative breast cancer (TNBC) [49,50]. Recent studies, however, have shown that miR-137 is upregulated in lung [51] and bladder cancer [52].…”
Section: Introductionmentioning
confidence: 99%
“…The relation between miR-137 and BC has been established in the last few years but the data is con icting. The levels of this miR were remarkably low in unfavourable TNBC [49,50], and at the same time there is an evidence of high levels of miR-137 in BC samples associated with a decrease patient survival [53]. miR-155 is upregulated in tumor tissue and performs as an oncogenic miRNA (oncomiR) in kidney [54], gastric cancer [55] and BC [14,56] ).…”
Section: Introductionmentioning
confidence: 99%